Regional Branding: Building Brand Value - Klára Margarisová; Lucie Vokáčová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
Regional branding is one of several ways to promote rural regions and support development of socially, culturally and environmentally oriented economies in areas that are interesting due to their natural and cultural heritage. The article attempts to review the conceptual and theoretical underpinnings of branding as conveyed by leading authors in the marketing field. The aim of this paper is to define brand as a broad complex of variables, which are used in building of its identity as a basis for creating value proposition and the position of a brand. Article briefly describes the most comprehensive labeling system for regional products at the micro-regional level is the one guaranteed by Association of Regional Brands (ARB). The main contribution of this article is a theoretical model of strategic management of a regional brand, which captures the interdependence of the individual steps of brand building as well as stakeholders. The starting point for building of brand value is a strategic analysis of the brand, including analysis of customer and competitors. The analysis of external factors is followed by analysis of the brand itself. The resulting relationship between the brand and the customer is based on value proposition representing benefits (functional, emotional, self‑expression). The concept of total product is connected with the concept of total brand and it is offered to the customer as a regional product. Finally it suggests possibilities for further research.